Literature in Primary Education. (Journal of Parents and Teachers, 2014)
One of the main objectives that they must achieve, at the end of the primary education stage, is competence in the areas of listening, writing, reading and speaking. However, these skills can be acquired through technological resources such as those set out in the following article. Some examples of this would be a database, word processor, etc. If you wish to continue learning, we invite you to read on.
Keywords: literature; resources; ICT; teacher; innovation; Primary education; competences